Chingyagee ipu (Manipuri Children's Literature) - Shamungou, Kh. (Smt.Kh.(O) Purnimashi, Nambol, 2013)
This book is a Children Novel based on the Environment of Secret Grove of Khoriphaba Hill.
Keywords: Manipuri; Chingyagee ipu; Children's Literature; Manipuri; Manipuri